2013
DOI: 10.1002/jeab.64
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation came first: Evolution and human cognition

Abstract: Contextual behavioral perspectives on learning and behavior reside under the umbrella of evolution science. In this paper we briefly review current developments in evolution science that bear on learning and behavior, concluding that behavior is now moving to the center of evolution studies. Learning is one of the main ladders of evolution by establishing functional benchmarks within which genetic adaptations can be advantaged. We apply that approach to the beginning feature of human cognition according to Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 147 publications
(149 reference statements)
2
43
0
2
Order By: Relevance
“…8 Future brain-imaging studies could certainly test this hypothesis by scanning participants while they completed AARRing tasks at different levels of relational development as specified by the MDML. Confirmatory evidence would be consistent with recent arguments that AARRing did not evolve in whole cloth, but emerged gradually in humans because it served to support and enhance intra-group cooperative activities (Hayes & Sanford, 2014;Hayes, Sanford, & Chin, 2016).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…8 Future brain-imaging studies could certainly test this hypothesis by scanning participants while they completed AARRing tasks at different levels of relational development as specified by the MDML. Confirmatory evidence would be consistent with recent arguments that AARRing did not evolve in whole cloth, but emerged gradually in humans because it served to support and enhance intra-group cooperative activities (Hayes & Sanford, 2014;Hayes, Sanford, & Chin, 2016).…”
supporting
confidence: 86%
“…Mutual entailing is thus conceptualized as the first, and a separate, level in the MDML. As an aside, recent conceptual analyses of the evolutionary origins of AARRing (Hayes & Sanford, 2014) have suggested that mutual entailing likely emerged first as an instance of a social act within a highly cooperative species (i.e., humans). Although plausible, the MDML was not designed to comport with any particular hypothesis of how AARRing evolved; mutual entailing is identified as a separate level of relational development within the MDML based simply on available data (albeit limited) within the existing RFT literature.…”
Section: Aarringmentioning
confidence: 99%
“…Viewing morality as a subset of cooperation is also consistent outside of behavior analysis (Tomasello & Vaish, 2013). Hayes, Gifford, and Hayes (1998) discuss the development of moral behavior from the perspective of RFT, which relates to a similar, more contemporary article on the evolution of cooperative behavior as is relates to language and cognition (Hayes & Sanford, 2014). By reviewing the role of language in cooperative and moral repertoires, a greater understanding about the origins and maintenance of volunteer behavior emerges.…”
Section: The Role Of Verbal Behaviormentioning
confidence: 94%
“…While some make the case that cooperative and altruistic acts occur among non-human species (Burkart, Fehr, Efferson, & van Schaik, 2007;Clutton-Brock, 2009), volunteering is a uniquely human activity, implying that verbal behavior plays a significant role in repertoire development and maintenance of elaborate prosocial and cooperative behaviors in humans (Hayes & Sanford, 2014). As previously discussed, volunteering rarely results in achieving the end goal, earning rewards, or even social recognition.…”
Section: The Role Of Verbal Behaviormentioning
confidence: 98%
“…Relational Frame Theory (RFT; Hayes, Barnes‐Holmes, & Roche, ) holds that arbitrarily applicable derived relational responding is the core response feature in verbal behavior and higher cognition (Hayes, Fox, Gifford, Wilson, Barnes‐Holmes, & Healy, ). Although specific types of “relational framing” are viewed as learned operants, the fact that relational framing can come under arbitrary contextual control, and involves altering the functions of events in relational networks, defines them as evolutionarily more recent forms of behavior (see Hayes & Sanford, this ).…”
mentioning
confidence: 99%